PENERAPAN MODEL VISUAL AUDITORY KINESTHETIC UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATEMATIKA KELAS IV - Septi Arinta Dewi; Wahyudi .; Endang Indarini (JURNAL HANDAYANI PGSD FIP UNIMED, 2018)
Abstract : Implementation of Kinesthetic Visual Auditory Models To Increase Activity And Learning Outcomes of Class IV Mathematics. The purpose of this study to improve student learning outcomes on mathematics subjects apply Kinesthetic Visual Auditory learning model. The result of the research shows the activeness of 14 students on the initial condition there are 6 students who have low category with 40% percentage, while the amount is 7 percentage 50% while for high activity only 1 student percentage 7%. Cycle I low category 1 students percentage 7%, moderate 7 berpresentase 50% category I students percentage 7%, moderate 7 berpresentase 50% category increased 6 students presentase 40%. Cycle II looks active 3 students persentage 20%, high 11 persentage 80%. Student learning outcomes beyond the KKM 14 students initial conditions 4 students completing percentage 28%, 10 students completeness 72% unfinished average 52. Cycle I 5 students who complete percentage 36% unfinished 9 percentage 64% average 58. Cycle II 12 students completed with 86% percentage unfinished 2 percentage 14% on average increase 77. Keywords: Activity, Learning Outcomes, Math, VAK (Visual Auditory Kinesthetic)Abstrak : Penerapan Model Visual Auditory Kinesthetic Untuk Meningkatkan Keaktifan Dan Hasil Belajar Matematika Kelas IV. Tujuan penelitian ini untuk meningkatkan hasil belajar matematika siswa dengan menerapkan model pembelajaran Visual Auditory Kinesthetic. Pada kondisi awal, 40% siswa memiliki keaktifan kategori rendah, ada 7 siswa yang memiliki kategori sedang dengan persentase 50% sedangkan untuk keaktifan yang tinggi hanya 1 siswa dengan persentase 7%. Siklus I kategori rendah ada 1 siswa dengan persentase 7%, kategori sedang 7 siswa dengan persentase 50%, sedangkan kategori tinggi ada 6 siswa dengan persentase 40%. Siklus II terlihat aktif kategori sedang 3 siswa dengan persentase 20%, tinggi 11 dengan persentase 80%. Hasil belajar siswa yang melampaui KKM 14 siswa kondisi awal 4 siswa yang tuntas persentase 29%, 10 siswa ketuntasan 72% tidak tuntas rata-rata 52. Siklus I ada 5 siswa yang tuntas dengan persentase 36% tidak tuntas 9 persentase 64% rata-rata 58. Siklus II berjumlah 12 siswa tuntas dengan persentase 86% tidak tuntas 2 persentase 14% rata-rata meningkatkan 77.Kata Kunci: Keaktifan, Hasil Belajar, Matematika, VAK ( Visual Auditory Kinesthetic)